Improving the Competitiveness of Micro and Small Enterprises through Production Cost and Business Feasibility Training: Synergy between Academics and the Cooperatives Office - Nihayatu Aslamatis Solekah; Ulfi Kartika Oktaviana; Safitri, Rini; Mardiana (Unram Journal of Community Service, 2025)
This community service program aims to improve MSMEs' understanding of calculating the cost of goods manufactured (HPP) and to analyze business feasibility. The focus is tailored to the needs of the target community. In the micro and small economic sector, Managerial and financial strengthening are often overlooked keys to increasing competitiveness. This activity was conducted face-to-face at the East Java Provincial Cooperatives Office using an interactive, simulation-based training approach and post-test evaluation. The results of the community service activity showed a significant increase in participants' understanding, demonstrated by their success in compiling cost of goods sold (COGS) calculation reports and analyzing business feasibility aspects. This activity represents the synergy between academics and the Cooperatives Office in fostering sustainable micro and small businesses.